Do combined sustainable agricultural intensification practices improve smallholder farmers welfare? Evidence from eastern and western Kenya - Nyarindo, Wilckyster Nyateko; Mugera, Amin; Hailu, Atakelty; Obare, Gideon Aiko (UoEm, 2024)
Smallholder farmers often bundle different sustainable agricultural intensification (SAI) practices to boost crop yield and address soil fertility challenges. However, there is a dearth of empirical studies that investigate farmers’ adoption of SAI bundles and their subsequent impacts. Using data from a three-wave panel survey of smallholder maize-legume producers in Kenya, we examine the adoption and payoffs from 10 SAI practices clustered into five dominant groups. We use a random effects multinomial logit model to determine the choice of SAI cluster at the plot level while controlling for unobserved individual heterogeneity. The results show that the number of extension contacts, farm labor availability, household wealth, and education of household heads positively and significantly affect the adoption of SAI clusters while renting plots and poor soil quality have negative effects. The multinomial endogenous treatment effects model results reveal significant variability in crop yield, total variable cost, revenue, and net income across the five SAI clusters. The benefits vary by crop system, region, and cropping year, indicating that a one-size-fits-all extension design is unsuitable for farmers. The study suggests the promotion of participatory extension policies that would allow locally adaptable and highly profitable bundles of SAI practices to be identified, refined, and disseminated
Keywords: clusters; multinomial endogenous treatment effects; sustainable agricultural intensification; welfare